2003
DOI: 10.1046/j.1442-2042.2003.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular metastasis from squamous cell carcinoma of the lung

Abstract: We present a case of squamous cell carcinoma of the testis that metastasized from lung cancer. The patient, who had received left pneumonectomy 2 years earlier for squamous cell carcinoma (SCC) of the lung, developed pulmonary metastasis, which was treated with chemotherapy. Although the recurrence regressed after treatment, the testicular tumor progressed gradually. Left radical orchiectomy was performed. Pathological examination revealed metastatic SCC. Testicular metastasis from lung cancer is a very rare d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…During our literature review, we found that there are 9 cases of lung cancer reported after this publication in 1989. Three of these cases were from autopsy series [ 7 ] and 5 of the remaining cases occurred approximately from 2 weeks to 2 years after diagnosis [ 5 , 6 , 8 - 10 ] while only one adenocarcinoma case presented with testicular tumor at the time of diagnosis [ 6 ]. To our knowledge, among 40 lung cancer cases reported, only one had adenocarcinoma presented with a testicular tumor at the time of diagnosis whereas our case is the first squamous cell cancer patient who presented with a testicular tumor at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During our literature review, we found that there are 9 cases of lung cancer reported after this publication in 1989. Three of these cases were from autopsy series [ 7 ] and 5 of the remaining cases occurred approximately from 2 weeks to 2 years after diagnosis [ 5 , 6 , 8 - 10 ] while only one adenocarcinoma case presented with testicular tumor at the time of diagnosis [ 6 ]. To our knowledge, among 40 lung cancer cases reported, only one had adenocarcinoma presented with a testicular tumor at the time of diagnosis whereas our case is the first squamous cell cancer patient who presented with a testicular tumor at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 6-7% of testicular neoplasms present as mass, and there is no lung cancer cases diagnosed with testicular mass although cases with testicular metastasis from lung cancer are available in the literature [ 2 - 4 ]. The adenocarcinoma of the prostate gland is the most common primary tumor whereas only a very small number of squamous cell carcinoma of the lung has been reported [ 5 , 6 ]. We present the case of a squamous cell carcinoma of the lung diagnosed with a testicular mass, which is very rarely seen in literature.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Smallman et al . concluded that the lower temperature of the scrotum may be an unacceptable environment for growth of metastatic tumor cells 5,6 …”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of testicular cancers are germ cell tumors that arise from the epithelium of the mature testis. Gonadal stromal tumors derived from cells that play a role in the development and maturation of sperm comprise approximately 5% of testicular tumors [ 2 ]. With the exception of lymphoma and leukemia cases, testicular metastases are extremely rare, and the majority of testicular neoplasms are primary tumors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent primary site that metastasizes to the testes is the prostate followed by lung [ 4 ]. However, there are few reports of testicular metastasis originating from squamous cell carcinoma of the lung [ 2 , 5 ]. Thus, in order to further the understanding of testicular metastasis and discuss the testis as a known sanctuary site, we present a case of testicular metastasis from squamous cell carcinoma of the lung.…”
Section: Introductionmentioning
confidence: 99%